Feasibility of an Instrument for Assessment of High Order Thinking Skills (HOTS) Material on Environmental Change for High School Students in Ambon City - Tuhumury, Benezia; Awan, Ali; Pattipeilohy, Mery (Program Studi Pendidikan Biologi, Pascasarjana, Universitas Pattimura, 2025)
High Order Thinking Skills (HOTS) is interpreted as the ability to think in complex processes in decomposing material, criticizing and creating solutions to problems. The low percentage of Higher Order Thinking Skills questions in the pre-observation results is an indicator of low cognition of students in school. This study aims to determine the feasibility and effectiveness of the assessment instrument for high order thinking skills (HOTS) environmental change material in class X of high school in Ambon City. This type of research is development (R&D) with a quantitative approach designed to obtain products in the form of HOTS question measuring tools. The research population is State Senior High School 3 Ambon, State Senior High School 5 Ambon and State Senior High School 11 Ambon with a sample of 103 students. The research instruments used are HOTS test question instruments and test instrument validation sheets. The data analysis technique uses a feasibility analysis of test instruments based on HOTS questions. The results of the study show that :The HOTS question instrument for environmental change material is very feasible to be used as an assessment instrument in high schools in Ambon City. This means that the HOTS question instrument is very worthy of being given to students. HOTS-based assessment instruments on environmental change materials are effectively used as assessment instruments in high schools in Ambon City, this can be seen from the ability of students to work on question item instruments that are assessed individually. The students' scores obtained from the results of working on the test items were then averaged to obtain one score as the result of the students' HOTS thinking abilities, namely 1.27 for State Senior High School 3 Ambon, 1.71 for State Senior High School 5 Ambon, and 1.82 for State Senior High School 11 Ambon.